2010
DOI: 10.1203/00006450-201011001-00698
|View full text |Cite
|
Sign up to set email alerts
|

698 Effects of Casein and Adaptedmilk Formula on the Proliferation of Lymphocytes, Mid-Cells and Granulocytes and on Circulting Lipids

Abstract: Background:The casein is the main protein that appears to be involved in childhood diseases caused by the consumption of adapted infant-milk formula (IMF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A microbiological analysis revealed that the diets had a significant effect on the growth and activity of various bacterial species in the intestinal ecosystem, and that lactic acid bacteria contributed to restoring intestinal microbial balance. Aribi et al (2010) determined the effects of casein and an adaptedmilk formula on the proliferation of lymphocytes, mid-cells and granulocytes and on circulating lipids in rabbits. The cited authors found that casein and the adapted-milk formula enhanced the activity of phagocytes, eosinophils and basophils, and inhibited lymphocyte proliferation.…”
Section: Caseinmentioning
confidence: 99%
“…A microbiological analysis revealed that the diets had a significant effect on the growth and activity of various bacterial species in the intestinal ecosystem, and that lactic acid bacteria contributed to restoring intestinal microbial balance. Aribi et al (2010) determined the effects of casein and an adaptedmilk formula on the proliferation of lymphocytes, mid-cells and granulocytes and on circulating lipids in rabbits. The cited authors found that casein and the adapted-milk formula enhanced the activity of phagocytes, eosinophils and basophils, and inhibited lymphocyte proliferation.…”
Section: Caseinmentioning
confidence: 99%